(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
High-temperature proton exchange membrane fuel cell (HT-PEMFC) systems operating on reformed methanol present a viable solution for decentralized power generation, offering benefits in fuel flexibility, system compactness, and thermal integration. However, optimizing their performance remains challenging due to the intricate coupling of thermochemical and heat recovery processes across multiple subsystems. In this study, an integrated combined cooling, heating, and power (CCHP) system is developed by thermally linking a reformed methanol HT-PEMFC with a double-effect LiBr–H₂O absorption refrigeration cycle. To maximize performance, a multi-objective optimization framework is established using the Non-Dominated Sorting Genetic Algorithm II (NSGA-II), targeting three conflicting objectives: maximizing exergy efficiency, minimizing exergy cost per unit product, and reducing specific CO₂ emissions. From the resulting Pareto-optimal set, the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) is applied to identify the most balanced operating scenario. The optimal solution achieves an exergy efficiency of 43.12%, a CO₂ emission rate of 0.510 kg/kWh, and an exergy cost of 167.59 USD/GJ—representing respective improvements of 20.73%, 17.10%, and 1.07% compared to a baseline configuration. The recommended operating ranges for critical parameters include a stack temperature of 173.94–179.91°C, a steam-to-carbon ratio of 1.78–1.80, a current density between 0.20–0.40 A/cm², and cathode stoichiometry from 2.29–2.52. These findings offer valuable insight into the design and operation of next-generation methanol-based tri-generation energy systems.